Social cost in construction projects - Celik, Tolga; Kamali, Saeed; Arayici, Yusuf (Elsevier Science Inc, 2017)
Despite the fact that completion of construction projects has a direct positive impact on the growth of national and local economies as well as humans' wellbeing, construction projects, especially in the urban areas, generate serious environmental nuisances for the adjacent residents and have unintentional adverse impacts on their surrounding environment. Construction causative adverse impacts on the neighbouring communities are known as the social costs. This study aims to present a state-of-the-art overview of social costs in construction industry in terms of definition, consideration, classification and quantification. Furthermore, it is aimed to bring the construction social cost phenomenon for the agenda of Environmental Impact Assessors. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Social cost; Construction costs; Construction management; Construction adverse impact; Social cost definition; Social cost quantification